On the formation of single and binary helium-rich sdO stars - Justham, S; Podsiadlowski, P; Han, Z (2010)
We propose a formation channel for the previously unexplained helium-rich subdwarf O (He-rich sdO) stars in which post-subdwarf B (sdB) stars (i.e. hybrid COHe white dwarfs) reignite helium burning in a shell after gaining matter from their helium white-dwarf (WD) companions. Such short-period binaries containing post-sdB WDs and helium WDs are predicted by one of the major binary formation channels for sdB stars. In the majority of cases, mass transfer is expected to lead to a dynamically unstable merger event, leaving a single-star remnant. Calculations of the evolution of these stars show that their properties are consistent with the observed He-rich sdO stars. The luminosity of these stars is about an order of magnitude higher than that of canonical sdB stars. We also suggest that binary systems such as PG 1544+488 (Ahmad et al. 2004) and HE 0301-3039 (Lisker et al. 2004), which each contain two hot subdwarfs, could be the outcome of a double-core common-envelope phase. Since this favours intermediate-mass progenitors, this may also explain why the subdwarfs in these systems are He-rich.